PENINGKATAN KEMAMPUAN MEMBACA PEMAHAMAN DENGAN MODEL CORE (CONNECTING, ORGANIZING, REFLECTING, EXTENDING) SISWA KELAS VIII 3 SMPN 1 KOTA BENGKULU - Susi Sales (Wacana: Jurnal Penelitian Bahasa, Sastra dan Pengajaran, 2016)
The purpose of this study to determine the increase of reading comprehension with model of CORE (connecting, organizing, reflecting, extending) VIII.3 grade students of SMPN 1 Kota Bengkulu. This research is a class act. Subjects in this study were students VIII.3 SMPN 1 Bengkulu city. The place and time of classroom action research (PTK) is in a class VIII.3 SMPN 1 Kota Bengkulu Indonesian and during school hours, ie Tuesday, March 15, 2016 and Thursday, March 17, 2016. Data collection techniques in this study is the testing techniques and observation techniques to Determine the average value and completeness of classical study. Based on the research that the Model CORE (connecting, organizing, reflecting, extending) can improve reading comprehension VIII.3 grade students of SMPN 1 Kota Bengkulu. It can be seen from the results of each action learning cycle. The results Showed increases the average value items, namely in cycle 1 students' average score is 69.41 good category and in cycle 2, the average value of students is 88.35 splendidly category. Increase in the average value of cycle 1 to cycle 2 was 18.94 score. Classical learning completeness students in cycle 1 38.24% in cycle 2 complete learn student 94.11%, an increase of in cycle 1 to cycle 2.Kata Kunci: Ability, Reading Comprehension, Model CORE